Triage and Protocol Recommendations for the Parasitology Laboratory Based on an Epidemiological Investigation of Parasite Diagnostics in Ontario Laboratories. Issue 6 (2014) - Maier, Allison; Krolik, Julia; Majury, Anna
Abstract : OBJECTIVES:A study was performed using a subset of Ontario laboratory parasitology data, with three objectives: to describe parasitic infections in Ontario; to identify risk factors for acquiring a parasitic infection using routinely collected information; and to use this information to assess current protocols for parasite testing in laboratories and, in turn, to propose alternatives to optimize the allocation of laboratory resources. METHODS: All parasitology records from January 4, 2010 to September 14, 2010 were reviewed descriptively and risk factor analyses were performed using information collected from requisitions. These results were used to develop preliminary alternative protocols, which considered high-throughput screening tests and inclusion/exclusion criteria for ova and parasite testing; these were then retrospectively analyzed with the dataset to determine appropriateness. RESULTS: Of the 29, 260 records analyzed, 10% were multiple samples from single patients submitted on the same day, of which 98% had the same result. Three percent of all parasite tests were positive, with the most prevalent parasites being (in ascending order) Dientamoeba fragilis, Giardia lamblia, Cryptosporidium species and Entamoeba histolytica / dispar . Age and sex were found to be weak risk factors, while rural living was found to be a moderate risk factor for D fragilis, G lamblia and Cryptosporidium infections. The strongest risk factor was travel history, especially for nonendemic parasites. The retrospective analysis of six alternative protocols identified four that may be more efficient than current procedures. CONCLUSIONS: The present study demonstrated that current protocols may be redundant and can be optimized to target prevalent parasites and populations with high risk factors.